Dietary Habits across the Lifespan and Risk of Prostate Cancer. A population-based study in Iceland - Jóhanna Eyrún Torfadóttir 1974- (2012)
Background and aims: Previous studies have provided evidence for the importance of early life environment in the etiology of prostate cancer (PCa). Here, the aim was to explore associations of food intake during different periods of life and risk of PCa. Design: A population-based cohort of 8,894 men born between 1907 and 1935 were followed for PCa diagnosis and mortality from entry (in waves from 1967 to 1987) through 2009. The participants provided information on early life residency – a marker for dietary habits. In 2002-2006, a sub-group of men aged 67-96 years, reported their dietary habits in the AGES-Reykjavik study. We used regression models to estimate odds ratios (ORs) and hazard ratios (HRs) for PCa according to early life residency and dietary habits. Models were adjusted for potential confounders. Results: During mean follow-up of 24.3 years, 1,123 men were diagnosed with PCa including 371 with advanced disease (stage 3+, or PCa death). Compared to early life residency in the capital area, rural residency, with high milk consumption, for the first twenty years of life, was marginally associated with increased risk of advanced PCa (HR = 1.29, 95% confidence interval (CI): 0.97-1.73); particularly among men born before 1920 (HR = 1.64, 95% CI: 1.06-2.56). Among the subgroup (n = 2,268), who provided dietary information, 347 had or were diagnosed with PCa during follow-up, 63 with advanced disease. In adolescence, rye bread consumption (daily vs. less) was associated with decreased risk of advanced PCa (OR = 0.47; 95% CI: 0.27-0.84) while milk consumption (daily vs. less) and high consumption of salted or smoked fish were associated with increased risk of advanced PCa (OR = 3.22; 95% CI: 1.25-8.28 and OR = 1.98; 95% CI: 1.08-3.62, respectively). None of the explored foods consumed in midlife were associated with PCa risk. In older age, fish oil consumption was associated with reduced risk of advanced PCa (HR = 0.43; 95% CI: 0.19-0.95) and high consumption of salted and smoked fish with increased risk ...